Pengembangan Video Pembelajaran Bahasa Jepang Berbasis Animaker untuk Meningkatkan Kemampuan Berpikir Kritis Siswa Jurusan Perhotelan di SMK Kota Singaraja - Md Marta Sari Dewi; Desak Made Sri Mardani; I Wayan Sadyana (Jurnal Penelitian Mahasiswa Indonesia, 2023)
This study aims to develop Animaker-based Video Animation learning media. The development of this learning media uses the Multimedia Development Life Cycle (MDLC) developed by Luther which consists of several stages, namely the Concept, Design, Material Collecting, Assembly, Testing and Distribution stages. Data collection was carried out through interviews and questionnaires in the form of expert test assessment questionnaires (media expert tests and material expert tests) and limited trials. In this research, used qualitative and quantitative data. Animated videos developed 9 themes that have been adapted to the needs of teachers by presenting vocabulary introductions, short conversations and practice questions that are able to guide students' abilities in critical thinking. The results obtained from the media expert test were 100 (very appropriate), from the material expert test, namely 84.09 (very appropriate). Then, the results obtained from the teacher's trial were 100 (very appropriate) and the limited trial from students was 96.66% (very feasible). Thus it can be concluded that the developed learning media can be used in Japanese language learning for Hospitality majors.